Parental Knowledge, Willingness, and Attitude towards Contraceptive Usage among Their Unmarried Adolescents in Ekpoma, Edo State, Nigeria - Airelobhegbe Dorcas Ehiaghe; Amadou Barrow (Hindawi Limited, 2022)
Background. Adolescence is a time of opportunity, vulnerability, and risk, particularly in relation to health, unsafe sexual activity, and reproductive health. Neglecting their reproductive health issues leads to a great risk of agonizing transition to parenthood, lifetime effects, and early pregnancy, which can compromise educational achievements and economic potentials. Meeting the reproductive health needs of adolescents mostly rests on the parents' shoulders. Thus, this study explored parental knowledge, willingness, and attitude towards contraceptive use among their unmarried adolescents. Methods. This was an analytical cross-sectional study design. The multistage sampling technique was used to recruit 360 parents from Ekpoma community, Edo State, Nigeria. A structured questionnaire was used to generate data for this study. Data processing and analysis were done using SPSS version 24. In order to determine association with outcome variables, chi-square (χ2) and Fisher's exact test statistics were used while statistical significance was set at p<0.05. Results. The proportion of parental knowledge on contraceptive methods was at 96.9%, parental willingness for their adolescents' contraceptive uptake at 31.7%, and positive attitude at 24.2%. Associated factors for parental knowledge of contraceptives include gender (χ2=8.655, p=0.003), age (†=13.377, p=0.001), marital status (†=133.730, p<0.001), educational level (†=103.689, p<0.001), religion (†=164.592, p<0.001), ethnicity (†=25.273, p<0.001), and duration of marriage (†=11.365, p=0.008). Factors such as educational level (†=21.220, p<0.001), marital status (†=9.001, p=0.022), and religion (†=6.058, p=0.046) were associated with parental attitude towards contraceptives for their unmarried adolescents. Education level (†=19.905, p<0.001) was associated with parental willingness for their unmarried adolescents' use of contraceptives. Conclusion. Although parents have good knowledge of contraception, this knowledge has not been passed on to their adolescents. However, few parents would encourage their adolescents to use contraceptives and advise the use of condoms if they are sexually active. Parents should be advised about contraceptive matters further to influence their adolescents' attitudes towards its usage. Establishing youth-friendly health centers will also encourage health information use and exposure.